COMPARATIVE 187RE-187OS SYSTEMATICS OF CHONDRITES: IMPLICATIONS REGARDING EARLY SOLAR SYSTEM PROCESSES - Walker R.J.; Morgan J.W.; Becker H.; Horan M.F.; Grossman J.N.; Rubin A.E. (My University, 2002)
A suite of 47 carbonaceous, enstatite, and ordinary chondrites are examined for Re-Os isotopic systematics. There are significant differences in the 187Re/188Os and 187Os/188Os ratios of carbonaceous chondrites compared with ordinary and enstatite chondrites. The average 187Re/188Os for carbonaceous chondrites is 0.392 ± 0.015 (excluding the CK chondrite, Karoonda), compared with 0.422 ± 0.025 and 0.421 ± 0.013 for ordinary and enstatite chondrites (1σ standard deviations). These ratios, recast into elemental Re/Os ratios, are as follows: 0.0814 ± 0.0031, 0.0876 ± 0.0052 and 0.0874 ± 0.0027, respectively. Correspondingly, the 187Os/188Os ratios of carbonaceous chondrites average 0.1262 ± 0.0006 (excluding Karoonda), and ordinary and enstatite chondrites average 0.1283 ± 0.0017 and 0.1281 ± 0.0004, respectively (1σ standard deviations). The new results indicate that the Re/Os ratios of meteorites within each group are, in general, quite uniform. The minimal overlap between the isotopic compositions of ordinary and enstatite chondrites vs. carbonaceous chondrites indicates long-term differences in Re/Os for these materials, most likely reflecting chemical fractionation early in solar system history.A majority of the chondrites do not plot within analytical uncertainties of a 4.56-Ga reference isochron. Most of the deviations from the isochron are consistent with minor, relatively recent redistribution of Re and/or Os on a scale of millimeters to centimeters. Some instances of the redistribution may be attributed to terrestrial weathering; others are most likely the result of aqueous alteration or shock events on the parent body within the past 2 Ga.The 187Os/188Os ratio of Earth’s primitive upper mantle has been estimated to be 0.1296 ± 8. If this composition was set via addition of a late veneer of planetesimals after core formation, the composition suggests the veneer was dominated by materials that had Re/Os ratios most similar to ordinary and enstatite chondrites.